MODULATION IN ENGLISH INTO INDONESIA TRANSLATION - Misbah, Hasanul (Department of English Education of STAIN Jurai Siwo Metro, 2014)
This descriptive-qualitative research investigated the modulation phenomena and measured the accuracy level of the phenomena occurring in the translated text. It involved 40 students at the fifth semester of English education program in STAIN Jurai Siwo Metro. The data were taken from each participantâs translated texts using observation and documentation. The kinds of text are scientific and literary texts. Both texts contain 20 modulation phenomena. All of the phenomena were analyzed by comparing the proper translation text with the translated text produced by the students and then measured in the term of accuracy level. The researcher found 11 Fixed Modulation (FM) and 9 Optional Modulation (OM). In the term of accuracy, the FM is more accurate than OM but OM has a lower inaccurate level than FM has. Related to the accuracy percentage of all phenomena, there are 16% categorized as accurate, 39% as less accurate, and 45% as inaccurate. In conclusion, the students are still lack of the accuracy in modulation so that they should be able to let themselves free from influential factors of the source language structure and to express natural and equivalent translation in target language